A New Amazonian Species of the Diminutive Frog Genus Adelophryne (Anura: Brachycephaloidea: Eleutherodactylidae) from the State of Amapá, Northern Brazil - Taucce, Pedro P. G. [UNESP]; Costa-Campos, Carlos E.; Haddad, Célio F. B. [UNESP]; De Carvalho, Thiago R. [UNESP] (American Society of Ichthyologists and Herpetologists (ASIH), 2020)
During recent field expeditions to an Amazonian region in eastern Guiana Shield (Serra do Navio, state of Amapá, northern Brazil), we collected and recorded calls of a species of Adelophryne, a diminutive leaf-litter-dwelling, direct-developing frog genus. After a careful integrative taxonomic evaluation using morphological, molecular, and bioacoustic data, we concluded that the series of specimens collected represent a new taxon, which we describe herein. The new species of Adelophryne is distinguished from all ten congeners by the following combination of character states: (1) male SVL = 12.5 mm; female SVL = 13.0-14.4 mm; (2) tympanic membrane present; (3) tympanic annulus present, incomplete; (4) vomerine teeth absent; (5) finger terminal discs absent; (6) tips of Fingers I-IV mucronate; (7) finger pads present (formula 1-1-2-1); (8) three phalanges in Finger IV; (9) dorsum smooth; (10) cloacal flap absent; (11) multi-note advertisement call composed of non-pulsed notes; (12) the call dominant frequency (4,802-5,706 Hz) coincides with the fundamental harmonic. Our study describes the eleventh species of Adelophryne, and, despite the increase in taxonomic knowledge within the past few years, there are still some species in the genus lacking a formal taxonomic description.